Adolescent learning and health behavior during the COVID-19 pandemic - Hariati Lestari (Public Health of Indonesia)
Background: COVID-19 pandemic, in its first year, forced restrictions on social, economic, work, education, and religious activities. All activities were diverted and conducted online to avoid exposure to the coronavirus. These online activities had an impact on students, particularly learning behavior and behavior related to health aspects.